2015
DOI: 10.1037/a0036005
|View full text |Cite
|
Sign up to set email alerts
|

A second look at the validity of widely used Rorschach indices: Comment on Mihura, Meyer, Dumitrascu, and Bombel (2013).

Abstract: We comment on the meta-analysis by Mihura, Meyer, Dumitrascu, and Bombel (2013), which examined the validity of scores in Exner's Comprehensive System (CS) for the Rorschach. First, we agree there is compelling evidence that 4 categories of cognitive scores-the "Rorschach cognitive quartet"-are related to cognitive ability/impairment and thought disorder. We now feel comfortable endorsing the use of these scores in some applied and research settings. Second, we conducted new meta-analyses (k = 44) for the 4 no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
94
2
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(99 citation statements)
references
References 47 publications
1
94
2
2
Order By: Relevance
“…
Wood, Garb, Nezworski, Lilienfeld, and Duke (2015) found our systematic review and meta-analyses of 65 Rorschach variables to be accurate and unbiased, and hence removed their previous recommendation for a moratorium on the applied use of the Rorschach. However, Wood et al (2015) hypothesized that publication bias would exist for 4 Rorschach variables.
…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…
Wood, Garb, Nezworski, Lilienfeld, and Duke (2015) found our systematic review and meta-analyses of 65 Rorschach variables to be accurate and unbiased, and hence removed their previous recommendation for a moratorium on the applied use of the Rorschach. However, Wood et al (2015) hypothesized that publication bias would exist for 4 Rorschach variables.
…”
mentioning
confidence: 98%
“…However, Wood et al (2015) hypothesized that publication bias would exist for 4 Rorschach variables. To test this hypothesis, they replicated our meta-analyses for these 4 variables and added unpublished dissertations to the pool of articles.…”
mentioning
confidence: 99%
“…Consequently, those Rorschach indexes that include FQ play an important role not only in the clinical setting, in which they can support diagnosis and help to understand the distress of the individual and on the prognosis and better treatment planning, but also in the research context. In fact, several recent studies have tested the psychometric properties of these indexes (Mihura, Meyer, Dumitrascu, & Bombel, 2013;Viglione, Giromini, Gustafson, & Meyer, 2014;Wood, Garb, Nezworski, Lilienfeld, & Duke, 2015), and applied them on several samples from different countries (DzamonjaIgnjatovic, Smith, Djuric Jocic, & Milanovic, 2013;Moore, Viglione, Rosenfarb, Patterson, & Mausbach, 2013;Silva & Costa, 2014). Valkonen, Lindfors, and Knekt (2012) used the Ego Impairment Index, EII, to study anxiety disorders, and found a significant, but weak association between the EII and the interview-based scale Level of Personality Organization, LPO, (Pyykkönen, 2008, apud Valkonen et al, 2012.…”
mentioning
confidence: 99%
“…Villemor-Amaral, Yazigi, Nascimento, Primi, and Semer (2007) examined location areas and their respective FQ of 370 Brazilian non-patient adult subjects with a view to the construction of a Brazilian Atlas of specific Localization Areas with their respective FQ list. The validity studies on FQ in the CS in Brazil were: Marques, Chaves, and Yazigi (2012) who examined psychiatric patients and found that the XA% variable, which combines FQ+, FQo and FQu, was sensitive to discriminate perceptual acuity in patients with psychotic features and non-psychotic patients, using both Exner's FQ listing (Exner, 1995(Exner, /1999 and the Brazilian FQ listing (Villemor-Amaral et al, 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation